2007 IEEE/ACM International Conference on Computer-Aided Design 2007
DOI: 10.1109/iccad.2007.4397244
|View full text |Cite
|
Sign up to set email alerts
|

Fast exact toffoli network synthesis of reversible logic

Abstract: Abstract-The research in the field of reversible logic is motivated by its application in low-power design, optical computing and quantum computing. Hence synthesis of reversible logic has become a very important research area in the last years. In this paper exact algorithms for the synthesis of generalized Toffoli networks are considered. We present an improvement of an existing synthesis approach that is based on Boolean Satisfiability. Furthermore, the principle limits of the original and the improved appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 21 publications
0
34
0
Order By: Relevance
“…In addition exploiting the higher level representation for problem specific strategies has to be considered in future work. As shown for example in [25] this may lead to further improvements.…”
Section: Discussionmentioning
confidence: 92%
“…In addition exploiting the higher level representation for problem specific strategies has to be considered in future work. As shown for example in [25] this may lead to further improvements.…”
Section: Discussionmentioning
confidence: 92%
“…These criteria make reversible logic synthesis a more challenging one. Exact synthesis methods, using Boolean satisfiability (SAT) [7], quantified Boolean formula (QBF) [8], dynamic programming [9], symbolic reachability [10], etc., can provide optimal solutions. In recent days, research in the area of reversible logic has been intensified and accelerated by the promising results.…”
Section: Related Workmentioning
confidence: 99%
“…In recent days, research in the area of reversible logic has been intensified and accelerated by the promising results. As a result, besides verification [11][12][13], testing [14][15][16], simulation [17,18], optimization [19], and debugging [20] and synthesis of reversible circuits [7], approaches exploiting permutations and truth tables [21] are main research areas. Minimizing the number of garbage outputs and number of gates are the major concerns in reversible logic circuits and it is observed that proposed 4 input ALG gate achieves minimum garbage output and leading to high speed and low power reversible circuits.…”
Section: Related Workmentioning
confidence: 99%
“…An exact synthesis method based on reachability analysis is described in [6]. In [3,4,20] approaches based on Boolean satisfiability (SAT) and in [22] a method employing Quantified Boolean Formula (QBF) satisfiability are used for exact synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…As the main objective the number of gates is minimized as done by many other researchers (see e.g. [5,9,11,15,16,20]). The proposed methodology can also be adapted for other gate libraries as well as other objectives.…”
Section: Introductionmentioning
confidence: 99%